1970
DOI: 10.1002/jcp.1040750108
|View full text |Cite
|
Sign up to set email alerts
|

An improved chemically defined culture medium for strain L mouse cells based on growth responses to graded levels of nutrients including iron and zinc ions

Abstract: Nutritional factors were evaluated for effects on growth of mouse fibroblast cells in suspension in a chemically defined medium. Quantitative requirements for each of the essential amino acids, choline, inorganic phosphate, iron, and zinc were established. An improved Chemically defined medium was formulated on the basis o f the findings yielding populations of L cells in excess of 5 x lo6 per ml without nutrient replenishment. When spent medium was replaced periodically, yields approaching 30 x lo6 cells per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…Murine L cells were cultured to confluency at 37 Њ C and 5% CO 2 in a chemically defined medium (37) to which 10% fetal bovine serum (Hyclone, Logan, UT) was added. Mock-transfected cells (designated as control) and cells transfected with cDNA corresponding to the pro-SCP-2 and SCP-x were obtained as described earlier (19,38).…”
Section: Cell Culturementioning
confidence: 99%
“…Murine L cells were cultured to confluency at 37 Њ C and 5% CO 2 in a chemically defined medium (37) to which 10% fetal bovine serum (Hyclone, Logan, UT) was added. Mock-transfected cells (designated as control) and cells transfected with cDNA corresponding to the pro-SCP-2 and SCP-x were obtained as described earlier (19,38).…”
Section: Cell Culturementioning
confidence: 99%
“…[5,6]), it has been suggested that inhibition of oligosaccharide-lipid synthesis in cells arrested in protein synthesis results because of a deficiency in dolichyl phosphate [3,4]. Such deficiency might occur in the absence of synthesis of acceptor polypeptides, since the lack of transfer of the oligosaccharide chain from the oligosaccharide-lipid to the acceptor polypeptide would preclude concomitant regeneration of dolichyl (di)phosphate.We have studied the regulation of glycoprotein synthesis in LM cells, a mouse fibroblast line that grows in suspension in chemically defined medium [7], thus allowing one to control conditions for exogenous polyisoprenoid supplementation. Labeling experiments in these cells in vivo indicate that the synthesis of mannose-labeled oligosaccharide-lipid was markedly inhibited in the presence of cycloheximide or puromycin.…”
mentioning
confidence: 99%
“…We have studied the regulation of glycoprotein synthesis in LM cells, a mouse fibroblast line that grows in suspension in chemically defined medium [7], thus allowing one to control conditions for exogenous polyisoprenoid supplementation. Labeling experiments in these cells in vivo indicate that the synthesis of mannose-labeled oligosaccharide-lipid was markedly inhibited in the presence of cycloheximide or puromycin.…”
mentioning
confidence: 99%
“…Y. pestis strain KIM D27 (wild type) (29) and the ⌬lcrV mutant (KLD29) (27) were grown in heart infusion broth (HIB), M9-Casamino Acids (M9-Ca) minimal medium, or thoroughly modified Higuchi's (TMH) medium (27,29,30). Y. enterocolitica strain W22703 (wild type) (31) and the ⌬lcrV mutant (CT1) (17) were grown in tryptic soy broth (TSB) or M9-Ca medium, as indicated.…”
Section: Methodsmentioning
confidence: 99%